Spectacle and Trumpism : an embodied assemblage approach - Miller, Jacob C. (Bristol shorts research., 2021)
This book advances new perspectives for critical thought by exploring the links between consumer culture and the post-truth politics of Trumpism, and how Trump embodies the frightening potential of capitalism to intersect with and enable fascistic forms of power.